نانسي فريزر: العدالة بين الجنسين نحو تصحيح المسار - الوالي، أمال Alwali, Amal; معافة، هشام (المركز الجامعي بلحاج بوشعيب عين تموشنت, 2023)
ما نرومه من هذا المقال هو تسليط الضوء على أحد أبرز رواد الفكر النسوي المعاصر وابنة الجيل الثالث لمدرسة فرانكفورت الفيلسوفة الأمريكية نانسي فريز Nancy Fraser، التي اهتمت بمفهوم العدالة الاجتماعية وخاصة ما تعلق بالعدالة الجندرية، فكانت رجما لولادة تصورات جديدة جمعت بين الأبعاد الاقتصادية التي لطالما كان التمييز الجنسي فيها واضحا إضافة إلى الجانب الثقافي والاعتراف بالهوية الأنثوية التي شهدت منذ القديم نوعا من التهميش والاحتقار. وفي هذا الإطار ابتعدت فريزر عن عدالة المساواة بين الجنسين لتضع جملة من المبادئ المتعلقة بالجوانب المادية والرمزية التي جعلت المرأة في موضع أدنى من الرجل. وعليه فقد شكلت نانسي فريزر فضاء ثورياً داخل الحركات النسوية ذاتها حاولت من خلاله القضاء على كل أشكال الظلم والهيمنة التي فرضها المخيال الذكوري من جهة والتي أسست لها النسويات أنفسهن بما في ذلك النسوية الليبرالية من جهة أخرى. The purpose of this article is to cast light on Nancy Fraser who is one of the pillars of contemporary feminist thought and amongst the third generation descendant of Frankfurt School. The American philosopher emphasizes Social Justice in her researches and looks for ways to achieve gender justice. Hence, the new postulations intertwined the economic dimensions and the recognition of the female identity. The former is characterized by sexual discrimination whereas the latter have witnessed a kind of marginalization and contempt. In the same vein, Fraser moves away from the concept of justice equality between genders by establishing a set of principles related to materialistic and symbolic factors that puts women in lower position than men. Nancy Fraser formed a revolutionary space inside the feminist movements themselves through which she attempts to eliminate all forms of injustice and domination were imposed by male society and were founded by liberal feminism as well.
Keywords: الفكر النسوي -- العدالة الاجتماعية -- الهوية الأنثوية -- حقوق المرأة -- فريزر، نانسي